Phenylalanine-arginine β-naphthylamide could enhance neomycin-sensitivity on Riemerella anatipestifer in vitro and in vivo - Liu, Shiqi; Liu, Junfa; Fu, Ning; Kornmatitsuk, Bunlue; Yan, Zhuanqiang; Luo, Junrong (Frontiers in Microbiology, 2023)
Riemerella anatipestifer is an important duck pathogen responsible for septicemia and infectious serositis, which has caused great economic losses to the duck industry. Phenylalanine-arginine β-naphthylamide (PAβN) is an efflux pump inhibitor, which mainly reduces the efflux effect by competing with antibiotics for efflux pump channels. Here, we found that R. anatipestifer strain GD2019 showed highly resistances to gentamicin, amikacin, kanamycin and neomycin. Notably, PAβN could significantly reduce the Minimal inhibitory concentrations (MICs) of neomycin on the GD2019 strain. Moreover, PAβN combined with neomycin significantly decreased bacterial loads, relieved pathological injury and increase survival rate (p < 0.05) for the ducks lethally challenged by the GD2019 strain. Therefore, our results suggested, in vitro and in vivo, PAβN could reduce neomycin-resistant of R. anatipestifer. Importantly, finding of this study provide a new approach for treating antibiotic-resistant R. anatipestifer infection.